Civil Law Analysis of Default in Land Sale and Purchase Agreements - Dewa Gede Bayu Permana (Ilmu Hukum Prima (IHP), 2026)
This study examines the issue of default in land sale and purchase agreements in Indonesia, focusing on the characteristics of default, effective and fair dispute resolution mechanisms, and the role of the principle of good faith in preventing and handling them. The method used is normative juridical with a literature review of the Civil Code, the Basic Agrarian Law, and related court decisions. The results show that default can take the form of various types of contract violations that have serious legal implications such as cancellation of the agreement and demands for compensation. Dispute resolution mechanisms include litigation and alternative channels such as mediation and arbitration that can improve efficiency and fairness. The principle of good faith is the main foundation in the implementation of agreements and dispute resolution to create trust and legal certainty. The study recommends strengthening regulations, legal education, and the development of alternative mechanisms to strengthen legal protection in land sale and purchase transactions in Indonesia.